New narratives of disability : constructions, clashes, and controversies - Green, Sara E. (Associate professor of sociology); Loseke, Donileen R., 1947- (Research in social science and disability, 2020)
This volume seeks to answer the call for richer, more diverse understandings of disability through questions about narrative frameworks in disability research. Narrative is a omnipresent meaning-producing communication form in social life that is both cultural and personal.